Monitoring of nosocomial infections as an element of prevention - Gąska, Izabela; Sygit, Katarzyna; Cipora, Elżbieta; Zukow, Walery; Karwat, Irena Dorota (Journal of Education, Health and Sport, 2017)
Introduction. Hospital infections are one of the most serious threats to the hospitalised patient and their monitoring is recognised as one of the most important criteria of care quality for modern hospitals. The aim of the work was to present the problem of nosocomial infections and desired behaviours and activities in the field of infection prophylaxis. Material and method. The analysis of the current scientific literature was carried out with particular attention to the prevention of infections in treatment wards and the need to monitor the patient’s condition and the environment in the case of an infection. Results. The lack of developed and implemented programmes for the control of nosocomial infections is a fundamental element that increases the risk of nosocomial infections. This disrupts the proper functioning of the hospital and causes additional health problems for the patient and the ward staff. In addition, the hospital suffers losses instead of savings, which is a priority aim in the current funding system. Conclusions. The basis for eliminating or minimising the incidence of nosocomial infections is a well-developed and implemented programme of hospital infection control based on the education of medical personnel in the field of infection prevention. Constant, comprehensive assessment of the procedures used and the standards of conduct, epidemiological data as well as microbiological data can ensure quick identification and elimination of the threat.